2014
DOI: 10.1371/journal.pone.0099974
|View full text |Cite
|
Sign up to set email alerts
|

The PXR rs7643645 Polymorphism Is Associated with the Risk of Higher Prostate-Specific Antigen Levels in Prostate Cancer Patients

Abstract: Levels of enzymes that determine testosterone catabolism such as CYP3A4 have been associated with prostate cancer (PCa) risk. Although some studies have related CYP3A4*1B allele, a gene polymorphism that modifies CYP3A4 expression level, with PCa risk, others have failed, suggesting that additional genetic variants may be involved. Expression of CYP3A4 is largely due to the activation of Pregnane X Receptor (PXR). Particularly, rs2472677 and rs7643645 PXR polymorphisms modify CYP3A4 expression levels. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…These observations led to the proposition that TERE1 controls the CPRC phenotype by regulating the endogenous levels of Vitamin K-2 and hence the transcriptional control of a set of steroid catabolism genes via the PXR. Other studies corroborate PXR in a similar role in prostate cancer (Kumar et al, 2010; Reyes-Hernandez et al, 2014; Zhang et al, 2010). …”
Section: Differential Role Of Pxr In Cancersupporting
confidence: 54%
See 1 more Smart Citation
“…These observations led to the proposition that TERE1 controls the CPRC phenotype by regulating the endogenous levels of Vitamin K-2 and hence the transcriptional control of a set of steroid catabolism genes via the PXR. Other studies corroborate PXR in a similar role in prostate cancer (Kumar et al, 2010; Reyes-Hernandez et al, 2014; Zhang et al, 2010). …”
Section: Differential Role Of Pxr In Cancersupporting
confidence: 54%
“…While some PXR polymorphisms did not seem to interact with cancer growth, progression, or drug response (Justenhoven et al, 2011; Martino et al, 2013; Tham et al, 2007), several others were found to be significantly associated with cancer risk, growth, progression, or therapeutic outcome. For instance, the PXR polymorphisms have been shown to be associated with increased lung cancer risk in smokers (Zhang et al, 2014a) (Zhang et al, 2014b), higher prostate-specific antigen levels in prostate cancer patients (Reyes-Hernandez et al, 2014), lymphoma risk (Campa et al, 2012), pharmacokinetics and pharmacodynamics of docetaxel and doxorubicin in breast cancer patients, pharmacokinetics and toxicity of irinotecan in colorectal cancer patients (Mbatchi et al, 2016), risk of colorectal cancer (Andersen et al, 2010), Barrett’s esophagus and esophageal adenocarcinoma (van de Winkel et al, 2011a), and docetaxel disposition in nasopharyngeal cancer patients (Chew et al, 2014). Hence, a complete mapping of PXR polymorphisms is required to fully understand the PXR activation in a variety of tumors.…”
Section: Future Directionsmentioning
confidence: 99%
“…A few studies have also shown that PXR has potential anti-inflammatory effects. Single-nucleotide polymorphisms linked to a decrease in PXR activity or expression level have resulted in inflammatory bowel disease in patients ( Langmann et al ., 2004 ; Dring et al ., 2006 ; Shah et al ., 2006 ; Reyes-Hernandez et al ., 2014 ; Zhang et al ., 2014 ). PXR-null mice were much easier subjected to colitis than wild-type mice ( Shah et al , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide and candidate gene based association studies in prostate cancer have attempted to elucidate the role of common risk alleles affecting disease susceptibility and aggressiveness [ 12 14 ]. But many of these were inconclusive as a sizable fraction of disease-associated SNPs were located in non-coding region while some of them suffered from lack of replicability in other populations [ 15 17 ]. Non-reproducibility of genetic association studies may be explained by multiple confounding factors such as, (a) a difference in risk allele frequency between populations, (b) divergent association of an allele with risk in different populations, and (c) possible interaction of an allele with other genetic or environmental factors that vary among populations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%